Stress and Burnout among medical students in hainan Island, China: A cross-sectional study - Houqian Shan; Zhaoxin Wang; Ling Yuan; Ning Chen; Maorui Yang; Di’er Cheng; Lei Sun; Zaijia Yang; Zhen Zhou; Shengfei Hou; Qingyu Wu; Hongpan Hou; et al. (PLoS ONE, 2025)
Background By 2025, the Hainan Free Trade Port is set to be fully operational, leading to a significant influx of foreign nationals into Hainan Island. This will drive a continuous increase in demand for healthcare human resources. However, many medical students currently struggle to complete their studies due to the perceived monotony of medical education and heavy academic workloads. Academic burnout has been identified as a major factor hindering students’ educational progress. Identifying factors influencing academic burnout in medical students during the early stages of their education may help reduce dropout rates. This study aims to investigate the current status of academic burnout among medical students in Hainan Province and explore associated socio-demographic factors, with the goal of providing evidence to strengthen the stability of healthcare workforce supply in Hainan, China. Methods The final sample consisted of 551 students from a medical university in Hainan Province, China. A cross-sectional survey was conducted from June 26 to July 7, 2024. Descriptive statistics, comparative analysis, and multiple linear regression analysis were employed to investigate factors associated with stress and academic burnout among medical students at the university. Results The mean academic stress score among respondents was 38.69 (SD = 7.88) of the participants. The mean academic burnout score was 59.96(SD = 11.03).Comparative analysis revealed no significant differences in stress levels across socio-demographic variables. However, disparities in academic burnout were observed based on:Only-child status, GPA,Maternal education level.Multiple linear regression identified predictors of academic burnout (F = 36.464, p < 0.001).Overall burnout: GPA < 2 (β = 0.120, p = 0.001), GPA 2–2.49 (β = 0.112, p = 0.002), Stress (β = 0.542, p < 0.001).The model explained 34.0% of burnout variance, with specific contributions to subdimensions:22.6% for Emotional Exhaustion,21.8% for Cynicism,29.7% for Low Academic Efficacy. Conclusions The findings reveal concerning levels of stress and academic burnout among medical students in Hainan Province. Significant disparities in burnout were observed across socio-demographic factors, including maternal education level, only-child status, and GPA. Stress and GPA demonstrated significant associations with academic burnout and its subdimensions emotional exhaustion, cynicism, and diminished academic efficacy. Targeted interventions to improve academic achievement among students with lower GPA may effectively alleviate burnout and subdimensions.